Effectiveness of Edible Coating to Extend Shelf-Life of Dry Fermented Sausage - N. P. Minh (Journal of Global Pharma Technology, 2016)
The manufacturing of rapid and shelf stable dry fermented sausages became an art and provided the market with a very diverse range of delicacies. Fermented sausages can be defined as a meat product made of a mixture of mainly pork meat pork fat, salt, curing agents, sugar, spices, and in many cases starter cultures are added. The mix, including as little oxygen as possible, is placed into steam - permeable casings and subjected to a fermentation and drying process. Fat is one of the important factors contributing to enhanced flavor, texture, juiciness, and mouth feel of dry fermented sausage. However, fat is easily rancid to create bad odor as well as lower product quality and shelf-life. Objective of the current research studied the feasibility of edible coating in extending shelf-life of dry fermented sausage. The dry fermented sausages were treated by different formulas (N0: control; N1: 2.0% wheat gluten; N2: 2.0% w/w chitosan; N3: 2.0% w/w sodium alginate; N4: 2.0% w/w collagen) and in different concentration of chitosan (2.0%, 2.5%, 3.0%, 3.5%, 4.0%). The effectiveness of edible coating was based on the physicochemical attributes such as pH, water activity (aw), TBARS value (mg/kg); biogenic amines such as tyramine (mg/kg), 2-phenylethylamine (mg/kg), tryptamine (mg/kg), cadaverine (mg/kg), putrescine (mg/kg) and histamine (mg/kg); antimicrobial capacities such as total plate count (cfu/g), Enterobacteriaceae (cfu/g), Coliform (cfu/g), E. coli (cfu/g), Staphylococus (cfu/g), Listeria (cfu/g), Salmonella (cfu/g), Vibrio (cfu/g), yeast (cfu/g), mold (cfu/g) and sensory characteristics of dry fermented sausage during storage. All treated samples were analyzed after 9 months of storage at ambient temperature under vaccum packing. Results revealed that the incorporation of 3.0% w/w chitosan could inhibit microbial spoilage and lipid oxidation and therefore maintain the sensory score of the dry fermented sausage for 9 months during storage. The study indicated that the combination treatment with edible coating could be commercially utilized to maintain the freshness and prolong the shelf‐life of the dry fermented sausage.Keywords: Dry fermented sausage, Wheat gluten, Chitosan, Sodium alginate, Collagen, Antimicrobial, biogenic amine, Sensory.